2012
DOI: 10.1155/2012/943957
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Electrochemical Detection of Glucose at Glucose Oxidase-Cobalt Phthalocyanine-Modified Boron-Doped Diamond Electrode

Abstract: Electrochemical detection of glucose was achieved at a glucose oxidase (GOx)-cobalt phthalocyanine (CoPc)-modified borondoped diamond (BDD) electrode without any additional electron mediator in the electrolyte solution. The surface of the hydrogen-terminated BDD thin film prepared by microwave plasma-assisted CVD was modified with 4-vinylpyridine (4VP) via photochemical modification. The 4VP-BDD was then immersed in a CoPc solution to obtain CoPc-BDD. A poly(pphenylenediamine) (PPD) thin film containing GOx wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…For example, the sensing of hydrogen peroxide has been extensively studied using metal phthalocyanines [ 6 8 ], and elegant work by Ozoemena et al [ 9 ] has shown that a cobalt phthalocyanine (CoPC)-cobalt (II) tetraphenylporphyrin (CoTPP)-glucose oxidase-Nafion ® layer modified glassy carbon can be usefully utilised for the sensing of glucose. Additionally similar work by Kondo et al [ 10 ] have reported a similar method utilising a boron-doped diamond electrode as the underlying electrode. Note that in both cases, electrocatalysis ( via the modified CoPC electrodes) towards the sensing of hydrogen peroxide produced from the enzymatic reaction is reported compared to the bare underlying/supporting electrode substrate [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, the sensing of hydrogen peroxide has been extensively studied using metal phthalocyanines [ 6 8 ], and elegant work by Ozoemena et al [ 9 ] has shown that a cobalt phthalocyanine (CoPC)-cobalt (II) tetraphenylporphyrin (CoTPP)-glucose oxidase-Nafion ® layer modified glassy carbon can be usefully utilised for the sensing of glucose. Additionally similar work by Kondo et al [ 10 ] have reported a similar method utilising a boron-doped diamond electrode as the underlying electrode. Note that in both cases, electrocatalysis ( via the modified CoPC electrodes) towards the sensing of hydrogen peroxide produced from the enzymatic reaction is reported compared to the bare underlying/supporting electrode substrate [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 97%
“…Additionally similar work by Kondo et al [ 10 ] have reported a similar method utilising a boron-doped diamond electrode as the underlying electrode. Note that in both cases, electrocatalysis ( via the modified CoPC electrodes) towards the sensing of hydrogen peroxide produced from the enzymatic reaction is reported compared to the bare underlying/supporting electrode substrate [ 9 , 10 ]. Other studies by Wring et al [ 11 ] have reported CoPC to be electrocatalytic towards the analytes coenzyme A and reduced glutathione.…”
Section: Introductionmentioning
confidence: 97%
“…In the presence of glucose anodic current began to flow at +0.20 V versus Ag/AgCl and almost constant at beyond +0.35 V (Figure 2A). This current response observed resulted from the electrochemical oxidation of H 2 O 2 , 25 which was generated by the GOx in biological microparticles (BSA-GOxMPs) that were not observed in the control BSA-MPs (Figure 2A, insert). This illustrates the retention of the biocatalytic function of BSA-GOxMPs due to the relatively mild microparticle fabrication conditions at neutral pH, room temperature, and in an aqueous environment.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The CoPc-modified BDD can also be applied to an electrochemical glucose sensor by covering a glucose oxidase/poly(p-phenylenediamine) layer on the surface. 18) Thus, surface modification to introduce appropriate surface functionalities is effective for the immobilization of functional molecules, such as biorelated molecules and catalysts. 19) Polyoxometalates (POMs) are discrete anionic metaloxygen clusters having a large variety of sizes, shapes, and nuclearities.…”
Section: Introductionmentioning
confidence: 99%